Digital Technology and Multicultural Parenting: A Case Study of Childcare Transformation in Pontianak: Transformation of Childcare in the Digital Era (Case Study of Pontianak Multicultural Society) - Junida, Dwi Surti (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study explores the impact of digital technology on childcare practices in Pontianak, a multicultural city in Indonesia. Employing a qualitative case study approach, the research involved purposively selected parents from six major ethnic groups (Malay, Dayak, Chinese, Javanese, Bugis, and Madurese). Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that digital technology significantly shapes parenting behaviors, with cultural and religious values strongly influencing parental decisions regarding technology use. For instance, Malay parents prioritize religious content, Chinese parents focus on academic tools, while Javanese and Bugis parents adopt more flexible approaches balancing digital use with social interaction. The study highlights how multicultural backgrounds shape diverse patterns of adaptation and perception toward technology in parenting. These insights contribute to the development of culturally responsive childcare and education policies in the digital age.